Survival and migration speed of radio-tagged Atlantic salmon (Salmo salar) smolts in two large rivers: one without and one with dams - Huusko, Riina; Hyvärinen, Pekka; Jaukkuri, Mikko; Mäki-Petäys, Aki; Orell, Panu; Erkinaro, Jaakko
2018